CWNA certified wireless network administrator official study guide - Coleman, David D. (Wiley, 2009)
"This valuable guide covers all objectives for the newest version of the PW0-104 exam, including radio technologies; antenna concepts; wireless LAN hardware and software; network design, installation and management; wireless standards and organizations; 802.11 network architecture; wireless LAN security; performing site surveys; and troubleshooting. Also included are hands-on exercises, chapter review questions, a detailed glossary, and a pre-assessment test"--Resource description page.
Includes bibliographical references and index. - Print version record
Keywords: Wireless communication systems; Electronic data processing personnel -- Certification; Wireless communication systems -- Study guides -- Examinations; Transmission sans fil; Transmission sans fil; Examens; Guides de l'étudiant; Electronic data processing personnel; Certification; Wireless communication systems; Examinations; Study guides; Study guides